If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2l + 10) = 48 Reorder the terms: 3(10 + 2l) = 48 (10 * 3 + 2l * 3) = 48 (30 + 6l) = 48 Solving 30 + 6l = 48 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 6l = 48 + -30 Combine like terms: 30 + -30 = 0 0 + 6l = 48 + -30 6l = 48 + -30 Combine like terms: 48 + -30 = 18 6l = 18 Divide each side by '6'. l = 3 Simplifying l = 3
| y+x=10-4 | | 3x+22=x+4 | | 0.6(x-1)+0.2x=6.6 | | y=-2.1x+3.4 | | -x-19=2x+8 | | 49=-7z | | y=2x^2-36x+c | | -2(x+2)+3=3(x+3)+4 | | (x-2)(x-2)+(y-6)(y-6)=25 | | 2+f=-3 | | x-6+x=78 | | -y/4=-16 | | 2x=960 | | x^3+4=13 | | -6(2t+8)=-108 | | 43+x=-37 | | x^4+5x^3-x^2-12x-6=0 | | 7x+21=3x+1 | | -6(27+8)=-108 | | b-38=-28 | | -3x^2+9x=2 | | 3(1.5+5y)=30 | | -6(27+8)=-180 | | 3(1+5y)=30 | | -11z=99 | | 2log(x)-Log(4)=Log(x+15) | | 3(5.0+5y)=30 | | 3/5÷2/5 | | 2p+q=15 | | h-47=-19 | | s/5=-30 | | 8+f=3 |